2002
DOI: 10.1007/s11886-002-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic blocking drugs as antifibrillatory agents

Abstract: Beta-Adrenergic blockade is associated with a significant reduction in mortality in most patients with structural heart disease. Clinical trial data involving patients after myocardial infarction or with congestive heart failure demonstrate that a reduction in sudden death accounts for much of the observed mortality reduction. Beta-adrenergic blockade inhibits the proarrhythmic effects of both neural and humoral sympathetic stimulation and inhibits the vagal withdrawal that accompanies ischemia. Although it do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Reduction in the incidence of sudden death is responsible (at least in part) for the survival benefit afforded by beta blockade in clinical trials (1). β-Blockers reduce arrhythmogenesis following infarction by attenuating both neural and humoral sympathetic actions (235,297,303). Several additional actions of β-blockers may contribute to their beneficial effects.…”
Section: β-Blockersmentioning
confidence: 99%
“…Reduction in the incidence of sudden death is responsible (at least in part) for the survival benefit afforded by beta blockade in clinical trials (1). β-Blockers reduce arrhythmogenesis following infarction by attenuating both neural and humoral sympathetic actions (235,297,303). Several additional actions of β-blockers may contribute to their beneficial effects.…”
Section: β-Blockersmentioning
confidence: 99%
“…In human and animal experiments, 23,24 β 1 ‐adrenoceptor antagonists have been shown to exert pronounced antifibrillatory effects in preventing the occurrence of ventricular tachycardia and ventricular fibrillation. Ogawa et al 25 .…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] β-blockers in general, and carvedilol in particular, may decrease mortality by a variety of mechanisms, including direct and indirect antiarrhythmic effects. [29][30][31] An early study revealed that carvedilol decreases the incidence of ventricular premature beats and nonsustained ventricular tachycardia. 32 A more recent doubleblind placebo-controlled study showed that the antiarrhythmic efficacy of carvedilol in patients with ischemic or nonischemic cardiomyopathy was paralleled by an improvement in ejection fraction independent of the etiology of heart failure.…”
Section: Clinical Correlationmentioning
confidence: 99%
“…35 In recent years interest has grown in examining the role of β-blockers in rate control and conversion to sinus rhythm in patients with atrial fibrillation. 31,38,39 Carvedilol is known to reduce morbidity and mortality and to improve hemodynamic status in patients with heart failure across a broad spectrum of clinical severity. Recent data indicate that these benefits extend to patients with chronic heart failure complicated by atrial fibrillation.…”
Section: Clinical Correlationmentioning
confidence: 99%